2009
DOI: 10.1029/2008gc002138
|View full text |Cite
|
Sign up to set email alerts
|

A model for the rheology of particle‐bearing suspensions and partially molten rocks

Abstract: [1] This contribution presents a semiempirical model describing the effective relative viscosity of crystalbearing magmas as function of crystal fraction and strain rate. The model was applied to an extensive data set of magmatic suspensions and partially molten rocks providing a range of values for the fitting parameters that control the behavior of the relative viscosity curves as a function of the crystal fraction in an intermediate range of crystallinity (30-80 vol % crystals). The analysis of the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
373
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(382 citation statements)
references
References 49 publications
(118 reference statements)
7
373
2
Order By: Relevance
“…Note that under the extreme conditions of the MO, it is unclear whether τMSS < τCS, or τMSS > τCS. In the former case (Ia), crystals remain entrained in the MO, but any mushy layers at the base of the MO should undergo efficient melt-solid segregation as soon as the rheological transition at crystal fractions of ~60% is reached (Abe, 1995;Arzi, 1978;Costa et al, 2009). In the latter case (Ib), crystals sink to the base of the MO, but efficient compaction of the orthocumulate layer (that consists of these crystals and interstitial MO liquid)…”
Section: Magma-ocean Freezing and Cumulate Fractionationmentioning
confidence: 99%
“…Note that under the extreme conditions of the MO, it is unclear whether τMSS < τCS, or τMSS > τCS. In the former case (Ia), crystals remain entrained in the MO, but any mushy layers at the base of the MO should undergo efficient melt-solid segregation as soon as the rheological transition at crystal fractions of ~60% is reached (Abe, 1995;Arzi, 1978;Costa et al, 2009). In the latter case (Ib), crystals sink to the base of the MO, but efficient compaction of the orthocumulate layer (that consists of these crystals and interstitial MO liquid)…”
Section: Magma-ocean Freezing and Cumulate Fractionationmentioning
confidence: 99%
“…Other experiments were conducted on synthetic magmas at high temperature and pressure (Caricchi et al, 2007), which were then built into a 355 model that considered the influence of crystals on a suspension viscosity (Costa et al, 2009). For consistency, we have accounted for the effect of crystals (and bubbles) on the relative viscosity (η r cr ) using the equations of Mader et al (2013), which are mainly based on Mueller et al (2010aMueller et al ( , 2011.…”
Section: Rheology Of a Melt-crystal Suspensionmentioning
confidence: 99%
“…The relative effect of bubbles on a melt has been well characterised by experiments on analogue 40 and natural samples (Bagdassarov andDingwell, 1992, 1993;Bagdassarov et al, 1994;Manga et al, 1998;Lejeune et al, 1999;Manga and Loewenberg, 2001;Llewellin et al, 2002a,b;Rust and Manga, 2002;Pal, 2003;Llewellin and Manga, 2005). These authors showed that bubble shape is strongly controlled by strain rate, which in turn affects the viscosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Etna eruptive style, in this study we combine two empirical models that allow us to account for the variation of silicate melt viscosity in the T (temperature)-X (composition)-H 2 O space and for the non-Newtonian rheological effects due to the presence of crystals in strained magmas (Costa et al, 2009). These models are applied to calculate the viscosity of volcanic products discharged during selected eruptive episodes of the January-June 2000 Mt.…”
Section: Introductionmentioning
confidence: 99%